2021
DOI: 10.1016/j.bcp.2020.114302
|View full text |Cite
|
Sign up to set email alerts
|

The comprehensive study on the therapeutic effects of baicalein for the treatment of COVID-19 in vivo and in vitro

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 46 publications
1
87
1
1
Order By: Relevance
“…Previous studies have demonstrated that baicalein, both in naked, as well as nanoparticle-encapsulated forms were biocompatible to human gingival epithelial cells [ 19 ]. Furthermore, from the systemic context, baicalein has demonstrated hepatoprotective properties [ 20 ]. There is evidence to show the anti-quorum sensing activity and biofilm inhibitory potential of Baicalein against Staphylococcus aureus [ 21 ], Avian Pathogenic E. coli (APEC) [ 22 ] and Candida albicans [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that baicalein, both in naked, as well as nanoparticle-encapsulated forms were biocompatible to human gingival epithelial cells [ 19 ]. Furthermore, from the systemic context, baicalein has demonstrated hepatoprotective properties [ 20 ]. There is evidence to show the anti-quorum sensing activity and biofilm inhibitory potential of Baicalein against Staphylococcus aureus [ 21 ], Avian Pathogenic E. coli (APEC) [ 22 ] and Candida albicans [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this nutraceutical agent alleviated the lesions of lung tissue and suppressed replication of SARS-CoV-2 in mice. Furthermore, this compound improved respiratory function and reduced inflammation, corroborated by decreasing the level of IL-1β and TNF-α in lipopolysaccharide (LPS)-induced acute lung injury of mice [ 246 ]. Docking evidence revealed that flavonoids biochanin A and silymarin strongly interact with the active site of SARS-CoV-2 spike glycoprotein and ACE2, respectively [ 247 ].…”
Section: Importance Of Phytochemicals In Combating Covid-19mentioning
confidence: 99%
“…Several studies have pointed out the anti-SARS-CoV-2 effects of S. baicalensis compounds, with an emphasis on baicalein and baicalin [36][37][38][39][40], wogonin [39], and oroxylin A [39].…”
Section: Ligand Preparationmentioning
confidence: 99%
“…Song et al [37] revealed that baicalein significantly inhibited replication of the virus and relieved the lesions of lung tissue in hACE2 transgenic mice infected with SARS-CoV-2. Moreover, Huang [41] noticed that baicalein and wogonin could be employed as the main active ingredients for the management of COVID-19 by targeting ACE2 and 3CLpro proteins.…”
Section: Ligand Preparationmentioning
confidence: 99%